Correlation of routine ultrasound features and BRAFV600E gene to the cervical lymph node metastasis of thyroid papillary carcinoma - Yu, LAN; SONG, Qing; Zhuang, JIN; ZHANG, Ying; LIN, Lin; Yu-kun, LUO (Jie fang jun yi xue za zhi, 2019)
Objective 　To investigate the correlation of routine ultrasound features and BRAFV600E gene to the cervical lymph node metastasis (CLNM) of thyroid papillary carcinoma (PTC). Methods 　A hundred and seven patients with thyroid papillary carcinoma who underwent thyroid gland resection and cervical lymph node dissection in the First Medical Center of Chinese PLA General Hospital from January to December 2018 were recruited as study subjects, including 56 patients in the metastatic group and 51 patients in the non-metastatic group. Ultrasound examination and BRAFV600E gene detection were performed, and the indicators obtained were compared between the two groups including gender, age, focus position (upper middle or inferior), close to the capsule or to the isthmus, focus located in the left or right lobes, single or multiple, maximum diameter, aspect ratio, boundary, shape, internal echo, internal components, peripheral halos, calcification, microcalcification, color Doppler features, Hashimoto's disease, and BR